Analisis Aspek Toleransi Dalam Film My Name Is Khan dalam Perspektif Pendidikan Islam - Sari, Kurnia Maya; Rahman, Rini; Nurjanah, Nurjanah (An-Nuha, 2023)
Islam is a religion for all people. One of the contents of Islamic teachings is about tolerance. Tolerance is an attitude of mutual respect, love and acceptance of differences. This study aims, (1) To analyze the aspects of tolerance that exist in the film My Name Is Khan in the perspective of Islamic education. (2) To find out the process of instilling the value of tolerance in the film My Name Is Khan in the perspective of Islamic education. This research method is a qualitative method with a content analysis approach. This type of research is library research. The results of this study are first, there are several aspects of tolerance in the film My Name Is Khan in the perspective of Islamic education including; recognizing the rights of others, respecting the beliefs of others, understanding each other, agreeing on differences, the Islamic concept of harmony and giving independence and freedom. Second, the process of cultivating the values of tolerance in the film My Name Is Khan in the perspective of Islamic education includes; introduce diversity, differences do not cause hatred, set an example, and tolerance for peace.